Philosophy and Theology in Late Antiquity: Some reflections on concepts and terminologies - Zachhuber, J (Brill, 2020)
The question of the relationship between nascent Christian thought in late antiquity and the philosophical tradition is neither new nor original. Of the various answers that have been proposed, however, many can be classified into a binary according to which Christian thought in the Patristic period is either seen as primarily opposed to philosophy or as strongly, potentially unduly, dependent on it. In this book chapter, I query this alternative and argue that it rests on an ultimately anachronistic distinction between philosophy and theology. Instead I seek to demonstrate that Patristic ‘theology’ can helpfully be understood in analogy to a philosophical school. By carefully examining the potential as well as the limitations of this analogy, my paper aims at an understanding of ancient Christian thought as fully embedded in its historical context while reckoning with its sui-generis character.